Additive fabrication of electrically controlled anepectic meshes - Parada, João Pedro Almodôvar (2020)
The present thesis documents the conceptual design and additive fabrication of composite anepectic meshes with incorporated wires that can induce a controlled temperature change through resistive heating by applying electric current. These anepectic meshes are characterized by having auxetic behaviour (negative Poisson’s ratio - NPR) in conjugation with a negative thermal expansion (NTE), composed of two distinct materials with none of the previous properties. Electrical tests took place with a hot plate beneath two glass plates, restraining the out-of-plane deformation of the sample, to carry out a preheating of the mesh, which was later considered essential to display anepectic behaviour. After electrical testing finished, image analysis was performed with the purpose of studying deformation in certain strategic points on the mesh to determine the coefficient of thermal expansion (CTE) at different temperatures. To evaluate heat dissipation and homogeneity, initial experiments were conducted alongside thermographic analysis. By adjusting wire positioning and including an extra power supply to the system, the heat dissipated from the heating element can be distributed more evenly throughout the entire mesh, which also enables a uniform deformation. Through optimized conditions and parameters, a peak CET value of −668 × 10−6 °C−1 was obtained for the regular scale mesh and −470 × 10−6 °C−1 for the smaller variant. Between the lowest and higher CET values, the highest difference was 500 for the regular scale mesh. Achieving a maximum electrical power (4A), this mesh was capable of deforming nearly 5% of its original form. Overall, the results of this thesis as a proof of concept confirms its feasibility and utility in biomedical applications where small and controlled deformation are necessary.